Analisis Tingkat Inflasi Dan Fluktuasi Harga Emas Terhadap Pembiayaan Gadai Emas (Studi Kasus Pada Bank Syariah Indonesia Kc Bogor Cibinong Periode 2021–2023) - Septy Putri Andini; Diah Yudhawati; Titing Suharti (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the effect of the inflation rate and fluctuations in the price of gold on gold pawning financing at Bank Syariah Indonesia KC Bogor Cibinong for the 2021-2023 period. The method used in this study is a descriptive quantitative method in the form of presentation of statistical results and data processing using Eviews 12 software including classical assumption tests, multiple linear analysis and hypothesis testing. The source of the data obtained from this study is secondary data through the original website of Bank Indonesia, the Precious Metals website and financial data reports on gold pawn financing of Bank Syariah Indonesia KC Bogor Cibinong. The results of this study show that partially the inflation rate has a significant effect on gold pawning financing with a tcount of 3.274 > 1.994 ttable and a probability value of 0.0036 <0.05. Meanwhile, fluctuations in the price of gold have no effect on financing pawn gold with a tcount of 0.771 < 1.994 ttable and a probability value of 0.4491 > 0.05. Simultaneously the rate of inflation and fluctuations in the price of gold affect the financing of gold pawning with an Fcount of 6.535 > 3.131 and a probability value of 0.0062 <0.05. It can be seen from the test of the coefficient of determination with an R-squared value of 0.332 or 33.2%, and the rest is influenced by other factors which are not included in the regression model.